Effects of starchy seed crystals on the retrogradation of rice starch. (15th July 2020) - Wang, Yunyun; Hu, Bing; Zhan, Jinling; Xu, Rui; Tian, Yaoqi
Highlights: Retrogradation properties of starch in presence of seed crystal were determined. B-type seed increased the recrystallization rate and the degree of crystal perfection. B-type seed made the unit cell more compact. A-type seed seemed to only loosen the unit cell. Abstract: This study aimed at exploring the effects of exogenous seed crystals on the starch recrystallization. A-type and B-type seed crystals from rice starch were added to rice starch paste during cooling to analyze the changes in retrogradation process. DSC results indicated that B-type seed improved the uniformity of crystal size and the degree of crystal perfection; it also affected the nucleation mode of retrograded starches at 4 °C, while A-type seed did not affect these properties. The XRD showed that the unit cell was compact, and the crystal grain became larger upon the introduction of B-type seed, while A-type seemed to loosen the cell. The SAXS reflected that B-type seed increased the thickness of the imperfect lamellar structure formed during recrystallization, while A-type seed decreased it. These findings might be due to the molecular segment arrangement on the nuclei growth surface affecting the arrangement of starch molecular segments approaching the nuclei.